Internal technology valuation: real world issues. (2011) - Thorn, Valerie; Hunt, Francis; Mitchell, Rick; Probert, David; Phaal, Rob
Although well-known, methods for valuing projects in the face of uncertainty, such as decision trees, do not seem to have been widely adopted by the industry. Despite the widespread academic confidence that they produce more realistic financial values than the naive use of discounted cash flow (DCF) techniques, managers appear to favour naivety over sophistication. In this paper, we propose one reason for this. We argue that the ambiguity (i.e., the uncertainty about the uncertainties) in most technology valuations prevents significant increases in confidence in the financial valuations produced by techniques more sophisticated than DCF, although there may be a better understanding of the underlying issues. We illustrate this argument by considering the uncertainties in a technology development at an SME. We then reflect on the role of financial valuations at the early stage in technology projects, suggesting that they are to help create a credible story rather than provide definitive figures. We then suggest some avenues for further research. First of all, however, we review the literature on uncertainty and ambiguity and on valuation of technology projects in the face of these challenges.